2001
DOI: 10.1097/00005373-200108000-00009
|View full text |Cite
|
Sign up to set email alerts
|

Blunt Cerebrovascular Injuries: Diagnosis and Treatment

Abstract: Increased awareness and aggressive screening have resulted in significantly increased incidence of diagnosis of CAI, with associated lower stroke-related mortality. VAIs have been noted with similar incidence, and though the stroke rate is lower with VAI, stroke outcomes are generally catastrophic. Anticoagulation therapy is effective for both varieties of BCVI.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

8
301
2
5

Year Published

2003
2003
2015
2015

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 293 publications
(316 citation statements)
references
References 14 publications
8
301
2
5
Order By: Relevance
“…The optimal treatment of BCVI has been a subject of debate. The use of systemic anticoagulation to reduce neurological complications of BCVI was first described by Fabian et al 26 and has been adopted as standard therapy in clinical practice 4,17,26,27 . Previous study has shown that in even in asymptomatic, untreated patients with BCVI, the rate of neurological complications can be as high as 21.5% 28 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The optimal treatment of BCVI has been a subject of debate. The use of systemic anticoagulation to reduce neurological complications of BCVI was first described by Fabian et al 26 and has been adopted as standard therapy in clinical practice 4,17,26,27 . Previous study has shown that in even in asymptomatic, untreated patients with BCVI, the rate of neurological complications can be as high as 21.5% 28 .…”
Section: Discussionmentioning
confidence: 99%
“…Blunt cerebrovascular injury affects approximately 1% of all blunt trauma admissions, and the reported incidence is as high as 2.7% in centres with aggressive screening protocols [1][2][3][4][5][6][7][8] . The pattern of BCVI consists of vascular transection, dissection, thrombosis, and formation of pseudoaneurysm or arteriovenous fistula (AVF) 9,10 .…”
mentioning
confidence: 99%
“…In more than 30% of cases, the diagnostics for BCVI are not started until a symptom caused by the vessel injury appears [20].…”
Section: Discussionmentioning
confidence: 99%
“…Because of an incidence of 0.24-1.03% in all casualties of blunt cerebrovascular injuries [5,7,12,20,21], a feasible screening algorithm which considers on factors and tracer diagnoses that determines a BCVI is strongly required. These factors and tracer diagnoses have been introduced by the Denver [6] and Memphis trauma groups [16] and have been used in many studies [8,13,14].…”
Section: Discussionmentioning
confidence: 99%
“…13 More recent evidence using a refined heparin regimen (target APTT of 40-50 s, no bolus) or anti-platelet agents in 39/ 50 patients with blunt VAI before the onset of ischaemia found a stroke rate of 2.6% compared to 54% in the untreated group. 14 In patients with vertebral artery injury and evidence of posterior circulation stroke, anticoagulation with heparin results in better outcomes and is recommended as treatment. 13 Current guidelines do not recommend screening of patients with cervical spine injuries for evidence of blunt vertebral or carotid artery injuries.…”
Section: Discussionmentioning
confidence: 99%